2015
DOI: 10.1080/17550874.2015.1065925
|View full text |Cite
|
Sign up to set email alerts
|

Winter gas exchange between the atmosphere and snow-covered soils on Niwot Ridge, Colorado, USA

Abstract: Background: There is a growing interest in understanding the gas exchange between the atmosphere and seasonally snowcovered regions, especially in light of projections that climate change will alter the timing and extent of seasonal snow cover. In snow-covered ecosystems, gas fluxes are due both to microbial activity in the snow-covered soils and to chemical and physical reactions with the various gases and/or dissolved constituents in the snowpack. Niwot Ridge, in the Colorado Rocky Mountains, has one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…We found that the wintertime monoterpene concentrations in the O-horizon were high, and were the same order of magnitude as those reported inside snowpack during winters (Aaltonen et al 2012). Microbial activity may lead to VOC production in the snowpack close to the soil surface (Liptzin et al 2015).…”
Section: Seasonal and Inter-annual Variationsupporting
confidence: 77%
See 1 more Smart Citation
“…We found that the wintertime monoterpene concentrations in the O-horizon were high, and were the same order of magnitude as those reported inside snowpack during winters (Aaltonen et al 2012). Microbial activity may lead to VOC production in the snowpack close to the soil surface (Liptzin et al 2015).…”
Section: Seasonal and Inter-annual Variationsupporting
confidence: 77%
“…Chamber flux measurements showed that some VOCs are released through the soil surface and snowpack into the atmosphere in December during continuous snow cover, which indicates that soil and snowpack are VOC sources or storages during wintertime. So far, there are only a very small number of other studies that have measured or estimated VOC fluxes during wintertime and more research is needed to relate soil VOCs to microbial processes (Aaltonen et al 2012;Liptzin et al 2015).…”
Section: Seasonal and Inter-annual Variationmentioning
confidence: 99%
“…Many researches have studied the influences of snow depth on CO 2 fluxes during the winter period 20,41 . They found that snow removal would cause a reduction of CO 2 fluxes, whereas snow addition would increase CO 2 fluxes (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, high-throughput sequencing technology can clearly describe the soil microbial diversities and composition. For example, Liptzin et al (2015) reported that in the Niwot area of Colorado, winter soil bacteria mainly included Cytophaga and Flexibacter, but the dominant microorganism under snowpack was SMF (snow mold fungi) 41 . Whether or not this conclusion is suitable for other regions has yet needed to be confirmed.…”
mentioning
confidence: 99%
“…We found that the wintertime monoterpene concentrations in the organic layer were high, and were in 25 the same order of magnitude as those reported inside snowpack during winters (Aaltonen et al, 2012). Microbial activity can lead VOC production in the snowpack close to the soil surface (Liptzin et al, 2015).…”
Section: Seasonal and Inter-annual Variationmentioning
confidence: 99%